Analisis Kualitas Air Tanah Dangkal untuk Keperluan Air Minum Di Kota Cimahi - Eka Wardhani; Luvina Oktavia Lukman Putri (Fakultas Teknik, 2021)
Groundwater is the primary source of clean water for Cimahi City residents. Groundwater quality has decreased due to contamination of domestic wastewater as it is managed through local systems that do not meet standards. This study aims to analyse the feasibility of shallow groundwater as a source of clean water in the town of Cimahi . The data used are secondary to the Environment Service for 2018. Sampling was conducted in 12 urban villages such as Citeureup, Pasir Kaliki, Cibeureum, Cibabat, Cipageran, Cimahi, Leuwigajah, Setiamanah, Cibeber, Baros, Karang Mekar, and Melong. There are 1 to 2 samples in each village . Based on field measurements, several parameters have not exceeded the required quality standards, namely turbidity, Manganese, Nitrate, MBAS Detergent, and Total Coliform. Groundwater quality from 20 sampling points only 4 points (20%) which meet the quality standards and are suitable as a water source, the remaining 16 sampling points (80%) are declared unfit for sampling because one to three parameters that do not meet the quality standards. Management can occur by improving the local system or by beginning to plan a centralized wastewater treatment system that uses piping to reduce groundwater contamination.